Metabolic rewiring directs melanoma immunology - Ningyue Sun; Ningyue Sun; Yangzi Tian; Yuhan Chen; Yuhan Chen; Weinan Guo; Chunying Li (Frontiers in Immunology, 2022)
Melanoma results from the malignant transformation of melanocytes and accounts for the most lethal type of skin cancers. In the pathogenesis of melanoma, disordered metabolism is a hallmark characteristic with multiple metabolic paradigms involved in, e.g., glycolysis, lipid metabolism, amino acid metabolism, oxidative phosphorylation, and autophagy. Under the driving forces of oncogenic mutations, melanoma metabolism is rewired to provide not only building bricks for macromolecule synthesis and sufficient energy for rapid proliferation and metastasis but also various metabolic intermediates for signal pathway transduction. Of note, metabolic alterations in tumor orchestrate tumor immunology by affecting the functions of surrounding immune cells, thereby interfering with their antitumor capacity, in addition to the direct influence on tumor cell intrinsic biological activities. In this review, we first introduced the epidemiology, clinical characteristics, and treatment proceedings of melanoma. Then, the components of the tumor microenvironment, especially different populations of immune cells and their roles in antitumor immunity, were reviewed. Sequentially, how metabolic rewiring contributes to tumor cell malignant behaviors in melanoma pathogenesis was discussed. Following this, the proceedings of metabolism- and metabolic intermediate-regulated tumor immunology were comprehensively dissertated. Finally, we summarized currently available drugs that can be employed to target metabolism to intervene tumor immunology and modulate immunotherapy.